2021
DOI: 10.1037/pne0000252
|View full text |Cite
|
Sign up to set email alerts
|

The strong versions of embodied cognition: Three challenges faced.

Abstract: The aim of this article is to discuss three challenges to the so-called “strong” versions of embodiment. The strong versions of embodied cognition (SVEC) have been successful in explaining how concrete concepts (e.g., pencil) may be understood based on sensory processes, yet they have failed to offer a comprehensive understanding of abstract concepts (e.g., freedom). In this regard, this article pinpoints three areas where the SVEC face limitations. First, the SVEC fail to fully support the active or passive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 140 publications
(161 reference statements)
1
11
0
Order By: Relevance
“…Another noticeable finding of this study was the significant similarity of the percentages of gesture usage between each category of metaphorical statements and its corresponding literal category. These results support the assumptions of the strong version of embodiment [ 11 ]: for a review, see [ 17 ]. These results suggest that each category of metaphors and its corresponding literal category are embodied in the same way.…”
Section: Discussionsupporting
confidence: 84%
“…Another noticeable finding of this study was the significant similarity of the percentages of gesture usage between each category of metaphorical statements and its corresponding literal category. These results support the assumptions of the strong version of embodiment [ 11 ]: for a review, see [ 17 ]. These results suggest that each category of metaphors and its corresponding literal category are embodied in the same way.…”
Section: Discussionsupporting
confidence: 84%
“…From an embodied perspective (Tirado et al, 2018;Khatin-Zadeh et al, 2021), these results could be attributed to PD patients' difficulty to access manipulable objects' semantic representation. Previous studies suggest that PD is associated with deficits in the semantic representation of actions/verbs that imply movement (Cardona et al, 2014;Bocanegra et al, 2015;Melloni et al, 2015;Suárez-García et al, 2021) or functional manipulability (Péran et al, 2009;Herrera et al, 2012;Bocanegra et al, 2017).…”
Section: Semantic Memory In Pdmentioning
confidence: 98%
“…This mediatory route may lead to the activation of those semantic features that are associated with the concrete concept. This idea is supported by the findings of a number of studies indicating that the processing of abstract domains involves the activation of concrete domains [40][41][42][43][44][45]. For example, the results of an experiment suggested that when subjects read words associated with powerful or powerless people, they performed better at recognizing letters in metaphor-congruent than in metaphor-incongruent spatial locations [46].…”
Section: Metaphor and Distributed Modelsmentioning
confidence: 79%